Variation in allele frequencies in benzimidazole resistant and susceptible isolates of Haemonchus contortus during patent infection in lambs - Michaela Urda Dolinská; Alžbeta Königová; Georg von Samson Himmelstjerna; Marián Várady (Scientific Reports, 2023)
Abstract We evaluated the variation in the frequency of benzimidazole (BZ) resistance-associated alleles at codons 200, 167 and 368 (F200Y, F167Y, V368L) of the β-tubulin isotype 1 gene during the patent period in isolates of Haemonchus contortus susceptible and resistant to BZ using pyrosequencing. Four lambs 5–6 months old were infected with 5000–6000 infective third-stage larvae (L3) of the susceptible MHco1 and the multi-resistant MHco4 isolates, respectively. Faecal samples were collected 28-times during 20–90 days post-infection (dpi). Coprocultures were subsequently prepared to produce L3 for genotyping. The frequency of the resistant allele (TAC) at codon 200 in MHco1 was lowest at 43 and 76 dpi with at each time point 0% and highest at 36 dpi with 10.85%, with a mean of 6.47% ± 2.39 and a coefficient of variation of 37.01%. The frequency of the TAC at codon 200 in MHco4 was lowest at 76 dpi with 25.6% and highest at 90 dpi with 49.25%, with a mean of 35.7% ± 4.42 and a coefficient of variation of 12.39%. No resistance alleles were detected in MHco1 at either codon 167 or 368. For MHco4 isolate, resistance alleles were detected only on codon 167 with a mean of 8.00% ± 4.83 and a mean coefficient of variation of 60.40%. Our results demonstrate the considerable variation in the frequency of resistant alleles in the susceptible and resistant isolates during the patent period. This variation should be considered when testing for the presence of BZ resistance in populations of gastrointestinal parasites, especially those with a low frequency of TAC.